Mid-term clinical outcomes of new generation drug-eluting stents for treatment of diffuse coronary artery disease - Ali Çoner; Davran Çiçek; Sinan Akıncı; Serhat Balcıoğlu; Cihan Altın; Haldun Müderrisoğlu (KARE Publishing, 2018)
Objective: Diffuse coronary artery disease (CAD) is a challenging issue in clinical cardiology practice. There are limited data about percutaneous revascularization in these patients. Methods: This study was an observational clinical evaluation. The records of patients with diffuse CAD revascularized with new-generation drug-eluting stents (DES) were researched retrospectively. Patients treated with multiple, overlapping new-generation DES (at least 60mm in length per vessel) were included. The incidence of major adverse cardiac events (MACE), defined as cardiac death, stent thrombosis, non-fatal myocardial infarction, and target lesion revascularization (TLR), at the end of the first year following the index procedure was recorded. Results: A total of 71 patients (with 75 coronary vessels) treated with new-generation DES for diffuse CAD were enrolled in the study. Zotarolimus-eluting stents were used in 48 vessels and biolimus A9-eluting stents were used in 27 vessels. The median total stent length per vessel was 75.0 mm (60.0-106.0) and the median number of stents implanted was 3 (2-4) for each vessel. The cumulative incidence of MACE at the end of the first year was 11.2% (8 patients). The presence of diabetes mellitus (DM) and ST-segment elevated myocardial infarction (STEMI) were defined as independent clinical risk factors related to MACE development. Conclusion: Coronary artery revascularization with new-generation drug-eluting stents can be a good choice in the treatment of selected patients with diffuse CAD. DM and STEMI were found to be related to poorer clinical outcomes with this treatment option in our study.